Anti-HIV-1 ADCC and HIV-1 Env Can Be Partners in Reducing Latent HIV Reservoir - Suryawanshi, Poonam; Bagul, Rajani; Shete, Ashwini; Thakar, Madhuri (Frontiers in Immunology, 2021)
Persistence of HIV reservoir even in suppressive ART is the key obstacle in HIV-1 Cure. We evaluated the ability of HIV-1 C Env to reactivate the latently infected resting memory CD4 cells and the ability of polyclonal HIV antibodies mediating ADCC to lyse the reactivated targets. HIV-1 antibodies from 25 HIV infected individuals (14 ADCC responders and 11 non-responders) were tested against the Env-C reactivated primary cells; CD4+ and CD4+CD45RO+ memory T cells in presence of autologous or heterologous effector cells using multicolour flowcytometry. The frequencies of p24+ve target cells were measured to determine the reactivation and antibody mediated lysis. Increase in the frequency of p24 expressing cells (P<0.01 in all cases) after Env-C stimulation of target cells indicated reactivation. When these reactivated targets were mixed with effector cells and HIV -1 antibodies, the frequencies of p24 expressing targets were decreased significantly when the ADCC mediating antibodies (P<0.01 in all cases) were added but not when the antibodies from ADCC non-responders or HIV negative individuals were added. In parallel, the NK cell activation was also increased only when ADCC mediating antibodies were added. The study showed that the HIV-1 Env could act as latency reversal agent (LRA) and only ADCC mediating antibodies could lyse the reactivated HIV reservoirs. The short stimulation cycle used in this study could useful in testing LRAs as well as immune mediated lysis of reactivated reservoirs. The observations have further implication in designing antibody mediated immunotherapy for eradication of latent HIV reservoir.